FINANCIAL MONITORING: SPECIFIC FEATURES AND IMPLEMENTATION FORMS - D. V. Karpuhin; A. V. Lapin (Финансы: теория и практика)
The article focuses on theoretical issues of the government control in the financial sector, the trends in legislation development, as well as forms and methods of financial monitoring. The recent decade has seen the rapid development of scientific concepts exploring financial control issues. The authors and leading scholars discuss the essence of the concept of “financial monitoring”, its characteristics and classifications. The legal regulation for financial monitoring purposes is rapidly developing along with academic approaches. The article offers a comprehensive review of trends in the development of the financial monitoring institution and genesis of legal regulation. The author suggests ways to improve the financial monitoring legislation. The methodological basis of the article uses the latest achievements in the cognitive theory. The study employed the following methods: general philosophical, systematic, analysis, synthesis, analogy, deduction, as well as traditional legal methods (formal-logical, comparative legal) and expert estimates. The main conclusion drawn from the results of the study is that there is a need to harmonize the forms and methods of control activities; systematize and unify risk analysis tools applied in the process of government control in the financial sector; amend the regulatory legislation, since financial monitoring is just a kind of government control. The novelty of the paper is in developing proposals towards further development of the financial monitoring institution.